2015
DOI: 10.17221/23/2015-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Picea abies provenance test in the Czech Republic after 36 years - Central European provenances

Abstract: ABSTRACT:Norway spruce (Picea abies [L.] Karst.) provenances from Central Europe (Hercynian-Sudetes area) were evaluated in a long-term experimental project (Germany-Czech Republic) 36 years after the outplanting. The growth characteristics, mortality and qualitative morphological characteristics of 64 spruce provenances were evaluated on the experimental plot Ledeč-Zaháj, in the Czech-Moravian Highland region of the Czech Republic, in typical conditions for Norway spruce cultivation. Results show 15-20% diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(63 reference statements)
1
10
1
Order By: Relevance
“…The result was well in accordance with the early results from provenance trials of the species [3, 19]. Ulbrichová et al [12] reported that environmental variables were significantly effective on growth characters in provenance test of Norway spruce. Significant site × provenance interaction was reported in a provenance test of Eucalyptus robusta [15].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The result was well in accordance with the early results from provenance trials of the species [3, 19]. Ulbrichová et al [12] reported that environmental variables were significantly effective on growth characters in provenance test of Norway spruce. Significant site × provenance interaction was reported in a provenance test of Eucalyptus robusta [15].…”
Section: Resultssupporting
confidence: 88%
“…These results indicated that there was a large variation among tested populations in growth at the examined test site and within species. However, while there were 15–20% differences for height and radial growth among provenances of Norway spruce, qualitative traits such as stem shape, branch density, and shape and health state were similar in the species [12] and had statistically significant difference (0.05 > p ) among populations of black pine reported by Gülcü et al [24] for growth characters. Scots pine provenances showed higher height and diameter performances than that of black pine and Taurus cedar which were natural forest tree species of the sites (Figures 3 and 4) opposite to primary results of the trial [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The easternmost provenance tests of Norwаy spruce grow in Western Europe (Pacalaj M. et al 2002;Matras 2009;Giertych 2009;Krajmerová et al 2009;Ulbrichová et al 2013Ulbrichová et al , 2015, but only a few provenances from Russia have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the IUFRO international experiment series has provided valuable information about population differentiation for growth and stem quality traits [18,19]. However, most of the studies have been conducted at young age [20], but the growth performance of provenances relative to each other can change over time [21][22][23], when affected by variable meteorological conditions and extreme events [24]. The evaluation of provenance experiments decades after establishment is rather rare.…”
Section: Introductionmentioning
confidence: 99%